Exploring the role of biogas systems in sustainable waste conversion and household energy supply - Chamdimba, Hope Baxter (Interaction, Community Engagement, and Social Environment, 2025)
Background: Systema 20 Model biodigesters were installed at Tsangano Market in Malawi and are being promoted all over the country. However, there is limited field-based proof to support their technical performance and social and environmental benefits. Therefore, this study assessed the technical performance of the biodigester and its community benefits. Methods: The study used a mixed-methods approach. Waste composition analysis involved randomly collecting and segregating 835.17 kg of market waste to determine its constituents; direct measurements of feedstock and water inputs and biogas and liquid biofertilizer yields were conducted using calibrated tools; household surveys (n = 385) and focus group discussions were conducted to examine cooking fuel use and firewood displacement by biogas; indoor emission reductions were estimated using WHO air quality guidelines; methane reductions were calculated using IPCC (2006) methods; and laboratory analysis and field experiments were conducted to assess biofertilizer quality and its effect on maize production. Findings: Organic waste accounted for 99.9% of market waste; biodigester produced 12 m³ of biogas and 548 litres of biofertiliser daily, with an operational efficiency of 57.7%; the plant has the potential to support 13 households with clean cooking fuel, displacing 37.1 tonnes of firewood annually and reducing indoor PM2.5 from over 300 µg/m³ to below 50 µg/m³; the system diverted 50.4 tonnes of organic waste yearly, avoiding 28.05 tonnes of CO₂-equivalent emissions; and the biofertiliser (200.02 m³/year) had the potential to produce 16 tonnes of maize annually, although it performed better under irrigation than rain-fed farming. Conclusion: The Systema 20 biodigester is a promising solution to waste, energy, and environmental challenges at the community level. However, further research is needed to address biodigester efficiency and sustainability bottlenecks. Novelty/Originality of this article: This study offers the first integrated field-based assessment of a market-scale biodigester in Malawi, linking energy production, environment, and food security.